A DISCURSIVE STRATEGY TO MAINTAIN THE CULTURAL ISLAM-POLITICAL ISLAM POWER RELATION IN INDONESIA IN TRIWIKROMO’S “LENGTU LENGMUA” (2012) - Sehla Rizqa Ramadhona (POETIKA, 2021)
This study aims to reveal the discursive play of the short story “Lengtu Lengmua” (2012) by Triyanto Triwikromo in maintaining the unequal power relation in Indonesia. The study is carried out on the basis of Norman Fairclough’s Critical Discourse Analysis that elaborates intertextuality theory and social theory of discourse. The research questions are what discourses influence “Lengtu Lengmua”’s celeng construction? and what political interests are supported and legitimized by “Lengtu Lengmua”’s celeng construction? It is a descriptive qualitative study for which data were collected using a note-taking technique. The relationships between data are elucidated by describing how the text of the short story, its production and the interpretation process are connected to the prevailing social conditions in Indonesia. The results show that: (1) “Lengtu Lengmua” represents, manipulates, negates, and transcends the discourse that sees that “celeng is a despicable animal” from the texts of Berburu Celeng (1998), Celeng Dhegleng (1998), and Tak Enteni Keplokmu (2000); and (2) to generate a notion of celeng as a noble animal, “Lengtu Lengmua” also configures the existing discourse conventions, namely conventions that are related to magical realism, Javanese society, children, Islamic shari’ah, and Islamic makrifat. These two results indicate that “Lengtu Lengmua” gives a new meaning to celeng and recontextualizes the celeng, which in previous texts is associated with human greed (i.e. capitalistic and corrupt), in religious issues especially those related to the contradiction between political Islam and cultural Islam. In turn, this discursive play has contributed to the formation of political Islam-cultural Islam power relation in recent years in Indonesia where cultural Islam occupies a dominant position. Penelitian ini bertujuan untuk mengungkap permainan diskursif cerpen “Lengtu Lengmua” (2012) karya Triyanto Triwikromo dalam pemertahanan relasi kuasa yang tidak setara di Indonesia. Kajian dalam penelitian ini mengacu pada Analisis Wacana Kritis dari Norman Fairclough yang mengelaborasi teori intertekstualitas dan teori sosial wacana. Pertanyaan yang ingin dijawab dalam penelitian ini adalah wacana apa yang memengaruhi konstruksi celeng “Lengtu Lengmua” dan kepentingan politik apa yang didukung dan dilegitimasi oleh konstruksi celeng “Lengtu Lengmua”. Kajian ini menggunakan metode penjabaran deskriptif kualitatif dan teknik pengumpulan data simak-catat. Hubungan antardata dikaji melalui deskripsi atau penjelasan bagaimana teks cerpen, proses produksi dan interpretasinya berkaitan dengan kondisi sosial yang melatar belakangi cerita dalam cerpen. Hasil penelitian menunjukkan bahwa (1) “Lengtu Lengmua” merepresentasikan, memanipulasi, menegasikan, dan melampaui wacana “celeng adalah hewan hina” dari teks Berburu Celeng (1998), Celeng Dhegleng (1998), dan Tak Enteni Keplokmu (2000); (2) “Lengtu Lengmua” juga mengonfigurasikan konvensi-konvensi wacana yang ada untuk menghasilkan konstruksi celeng sebagai hewan mulia, yaitu konvensi wacana realisme magis, masyarakat Jawa, anak-anak, Islam syariat, dan Islam makrifat. Kedua hasil penelitian ini menunjukkan bahwa “Lengtu Lengmua” memberikan makna baru atas celeng dan membawa representasi celeng, yang pada teks-teks sebelumnya diidentikkan dengan kerakusan manusia yang kapitalistik dan korup, ke dalam konteks persoalan keagamaan khususnya yang terkait dengan pertentangan antara Islam politik dan Islam kultural. Pada gilirannya, permainan diskursif ini berkontribusi pada pembentukan relasi kuasa Islam politik-Islam kultural pada tahun-tahun terakhir di Indonesia di mana Islam kultural menduduki posisi yang dominan.